Multiple cardiac myxofibrosarcomas with complete right pulmonary artery occlusion: a case report - Zhang, Weimin; Tang, Qi; Bolathan, Balhen; Xing, Yan; Sun, Xiaoxin; Huo, Qiang (Frontiers in Oncology, 2023)
Primary cardiac myxofibrosarcoma (MFS) is a rare form of cardiac malignant tumors. MFS usually involves the left atrium and presents as a unicentric or multicentric tumor mass. We reported on a 37-year-old female who presented with chest tightness and dyspnea for a month, dry cough, and occasionally having blood streak sputum for half a month. Echocardiography, cardiac computed tomography (CCT) and cardiac Positron emission tomography (PET) revealed multiple tumors in the heart. The right ventricle and right pulmonary artery were involved, with occlusion of the right pulmonary artery. Cardiac tumors were surgically resected and were consistent with low-grade MFS. No recurrence or metastasis occurred at 12 months of follow-up.